PENGARUH STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN, UKURAN DEWAN KOMISARIS TERHADAP KINERJA KEUANGAN PERUSAHAAN PUBLIK SEKTOR JASA KEUANGAN (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACT The purpose of an established company is to make a profit by maximizing the company's resources, therefore a company must have good financial performance. The role of financial managers is very influential on company performance. The importance of the role of the financial manager depends on the size of the company he works for. The size of the company is a measure of the size of a company and is one of the criteria considered by investors in an investment strategy. The size of the board of commissioners determines the effectiveness of monitoring the company's financial performance. This study analyzes the effect of Ownership Structure, Company Size and Board of Commissioners Size on the Financial Performance of Public Service Sector Companies that are listed on the Indonesia Stock Exchange in 2016-2018. The sample in this study was 44 companies. Based on the test results that simultaneously Managerial Ownership, Company Size, and Board of Commissioners have an influence on Financial Performance as measured by Earning Per Share. Partial testing shows that the variable Managerial Ownership, Company Size and the Board of Commissioners influence Earning per Share.Keywords: managerial ownership, company size, board of commissioners and earnings per share.